Drumming-associated anthrax incidents: exposures to low levels of indoor environmental contamination. Issue 12 (4th July 2018) - Bennett, E.; Hall, I. M.; Pottage, T.; Silman, N.J.; Bennett, A.M.
Abstract: Two fatal drumming-related inhalational anthrax incidents occurred in 2006 and 2008 in the UK. One individual was a drum maker and drummer from the Scottish Borders, most likely infected whilst playing a goat-skin drum contaminated with Bacillus anthracis spores; the second, a drummer and drum maker from East London, likely became infected whilst working with contaminated animal hides. We have collated epidemiological and environmental data from these incidents and reviewed them alongside three similar contemporaneous incidents in the USA. Sampling operations recovered the causative agent from drums and drum skins and from residences and communal buildings at low levels. From these data, we have considered the nature of the exposures and the number of other individuals likely to have been exposed, either to the primary infection events or to subsequent prolonged environmental contamination (or both). Despite many individual exposures to widespread low-level spore contamination in private residences and in work spaces for extended periods of time (at least 1 year in one instance), only one other individual acquired an infection (cutaneous). Whilst recognising the difficulty in making definitive inferences from these incidents to specific residual contamination levels, and by extending the risk to public health, we believe it may be useful to reflect on these findings when considering future incident management risk assessments and decisions in similar incidents that result in low-level indoor contamination.